Diversification, vertical integration, and industry analysis: New perspectives and measurement - Davis, Rachel; Duhaime, Irene M. (Strategic Management Journal, 1992)
Abstract Vertical integration, diversification, and industry analysis are fundamental topics in strategic management content research. We develop the conceptualization of these issues by exploring their nature as well as their correct measurement. Toward these ends, we conduct an extensive analysis of the COMPUSTAT II data base and the TRINET data base in all three research contexts. In addition to these two data bases, we also evaluate the Census of Manufacturers, S&P's Financial Dynamics , S&P's Industry Surveys and Dun and Bradstreet's Industry Norms and Key Business Ratios , for purposes of industry analysis. Important contributions include our identification of the potential of COMPUSTAT 11 data to distinguish within‐stage forward and backward vertical integration, and between‐stage forward and backward vertical integration, as well as our recommendations for the protection of the integrity of studies based on the COMPUSTA T II and TRINET data bases.